Magnesium-halobenzene bonding: mapping the halogen sigma-hole with a Lewis-acidic complex - Friedrich, Alexander; Pahl, Jürgen; Eyselein, Jonathan; Langer, Jens; van Eikema Hommes, Nico; Görling, Andreas; Harder, Sjoerd (Chemical Science, 2021)
Complexes of the Lewis base-free cations (MeBDI)Mg+and (tBuBDI)Mg+with Ph-X ligands (X = F, Cl, Br, I) have been studied (MeBDI = HC[C(Me)N-DIPP]2andtBuBDI = HC[C(tBu)N-DIPP]2; DIPP = 2,6-diisopropylphenyl). For the smaller β-diketiminate ligand (MeBDI) only complexes with PhF could be isolated. Heavier Ph-X ligands could not compete with bonding of Mg to the weakly coordinating anion B(C6F5)4−. For the cations with the bulkiertBuBDI ligand, the full series of halobenzene complexes was structurally characterized. Crystal structures show that the Mg⋯X-Ph angle strongly decreases with the size of X: F 139.1°, Cl 101.4°, Br 97.7°, I 95.1°. This trend, which is supported by DFT calculations, can be explained with the σ-hole which increases from F to I. Charge calculation and Atoms-In-Molecules analyses show that Mg⋯F-Ph bonding originates from electrostatic attraction between Mg2+and the very polar Cδ+-Fδ−bond. For the heavier halobenzenes, polarization of the halogen atom becomes increasingly important (Cl < Br < I). Complexation with Mg leads in all cases to significant Ph-X bond activation and elongation. This unusual coordination of halogenated species to early main group metals is therefore relevant to C-X bond breaking.
CRIS-Team Scopus Importer:2021-03-19